2012
DOI: 10.1111/j.1750-3841.2012.02906.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Antioxidant Packaging Material by Applying Corn‐Zein to LLDPE Film in Combination with Phenolic Compounds

Abstract: Zein protein, a by-product of corn processing industry, was laminated into plastic films in combination with natural phenolic compounds to develop antioxidant packaging films. The films demonstrated their efficient release patterns of antioxidant compounds, which are suitable for packaging applications and food protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(41 citation statements)
references
References 41 publications
3
37
0
1
Order By: Relevance
“…Amylose is water insoluble and the main source of our dietary fiber component whereas amylopectin is water-soluble. The presence of amylose makes starch insoluble while amylopectin allows starch to swell in aqueous phase to produce aqueous suspension which can be used to produce biodegradable environmental friendly films with several applications in food and pharmaceutical industries (Kaur et al 2013) In recent years, there have also been increased concerns about food quality and safety, which have motivated the development, in addition to biodegradable packaging, of active packaging that interact with food and assist in its conservation (Park et al 2012;Silva-Weiss et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Amylose is water insoluble and the main source of our dietary fiber component whereas amylopectin is water-soluble. The presence of amylose makes starch insoluble while amylopectin allows starch to swell in aqueous phase to produce aqueous suspension which can be used to produce biodegradable environmental friendly films with several applications in food and pharmaceutical industries (Kaur et al 2013) In recent years, there have also been increased concerns about food quality and safety, which have motivated the development, in addition to biodegradable packaging, of active packaging that interact with food and assist in its conservation (Park et al 2012;Silva-Weiss et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Zein films may serve as carriers for antioxidant compound in food packaging applications (Arcan & Yemenicioğlu, 2011;Forato, Britto, Scramin, Colnago, & Assis, 2013;Park et al, 2012). In zein films, for instance, the addition of gallic acid, p-hydroxy benzoic acid, ferulic acid, flavone, (+)-catechin, and quercetin (Arcan and Yemenicioğlu, 2011), butylated hydroxyanisole and butylated hydroxytoluene (Kleen, Pauda, & Engeseth, 2002), green tea extract (Lee, Lee, & Song, 2004), gallic acid (Neo et al, 2013), and ferulic acid and gallic acid (Cheng et al, 2015) have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Os filmes contribuíram também para reduzir a oxidação lipídica e off-flavors em embalagens de costeletas de carne suína pré-cozidas, prolongando o shelf life durante o armazenamento (CUTTER, 2006). Recentemente, o sucesso da inibição da oxidação lipídica e a estabilidade de cor foram efetivos através da aplicação de filme de zeína laminada similar ao plástico com compostos fenólicos naturais para embalagem de carne fresca moída (PARK et al, 2012).…”
Section: Formas De Extração De Zeína Do Milhounclassified